Correlations between fatty acids and key aroma compounds in roasted beef cuts for flavor customization - Wang, Ningbo; Zhong, Yingying; Zhu, Haiqiang; Zhao, Haiying (Frontiers in Nutrition, 2026)
Lipids are crucial determinants of the flavor and nutritional quality of meat. However, a deep understanding of how specific fatty acids direct the formation of key aroma compounds during thermal processing remains a challenge. This study employed an innovative fatty acidomics approach combined with HS-SPME-GC-TOFMS to systematically investigate the relationship between the lipid composition of six beef cuts (with three biological replicates per cut) and the volatile aroma profiles generated upon roasting. Multivariate statistics and correlation network analysis revealed that ultra-long-chain saturated fatty acids (C21:0, C22:0) showed strong positive correlations with fruity and cheesy aroma-related ketones (2-octanone, 2-heptanone), while the monounsaturated fatty acid C18:1n9c was significantly correlated with mushroom-alcohol (1-octen-3-ol). These flavors were formed through thermal degradation of saturated fatty acids and the specific 10-hydroperoxide cleavage of oleic acid. Conversely, polyunsaturated fatty acids such as C20:3n3 and C18:2n6t exhibited a significant negative correlation with dimethyl trisulfide, an undesirable sulfurous off-flavor compound. This suggests a competitive inhibition mechanism whereby rapid PUFA oxidation consumes reactive intermediates, thereby suppressing the Maillard reaction pathway responsible for off-flavor formation. Our findings provide novel biochemical insights into how the lipid matrix directly generates positive flavors and indirectly shapes the overall aroma profile. This work provides a theoretical basis for the targeted customization of beef flavor through precise regulation of lipid composition, aligning with the growing demand for nutrition-oriented and sensorially optimized foods.